Transcription profiling reveals co-regulation mechanism of gene expression related to growth and mineralization induced by pearl cultivation in Hyriopsis cumingii - Chen, Yige; Yao, Yuanbin; Shen, Xiaoya; Fu, Yuanshuai; Bian, Xiangli; Li, Wenjuan; Liu, Shijun (Frontiers in Marine Science, 2024)
Hyriopsis cumingii is a major freshwater pearl mussel in the world. In order to investigate the functional roles of the growth- and mineralization-related genes involved in the pearl formation process after the inserting nucleus into the mantle tissue of H. cumingii, we conducted a transcriptome analysis of data from different time periods after the pearl-nucleus insertion. We screened a total of 1,898 growth-related unigenes and 716 mineralization-related unigenes, including 12 growth-related differential genes and eight mineralization-related differential genes that showed sustained differential expression throughout the pearl formation. The results of the gene expression patterns among samples at different time points showed that the Mcon group and the M05d group clustered together, the M50d group and the M90d group clustered together, while the M20d group clustered separately. The overall density distribution of differential gene analysis at different periods after pearl-nucleus insertion of H. cumingii, cluster analysis, differential gene analysis, differential gene differential, and co-expression analysis together revealed that growth and mineralization-related genes have the same expression pattern and jointly regulate pearl formation. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment revealed that the same functional cluster and pathway were together present on the enrichment results of both growth- and mineralization-related genes, suggesting a synergistic effect between growth and mineralization. We found that genes such as bone morphogenetic proteins (BMPs) and calmodulin (CALM) are jointly involved in growth and mineralization processes. The study indicate that growth genes cooperate with mineralization genes to play biological roles in the early process of pearl formation in H. cumingii.